Professional Career Planning of Management Graduates in Pokhara - Adhikari, Nabin Bahadur (Journal of Nepalese Business Studies, 2023)
A critical component of management graduates’ future success and work happiness is the planning of their professional careers. In order to better understand how several elements, including as those related to family, personal interests, financial rewards, peer influences, and motivation to work, this study looked at how management graduates in Pokhara planned their professional careers. A 285 management graduates from various institutions and colleges located within Pokhara Metropolitan city were participated in questionnaire survey. This study’s methodology is an analytical and casual comparative research design. There are positive correlation between career planning of management graduates and family related factors (.274), career planning and personal interest (.059), career planning and financial benefits (.092), career planning and peer influences (.499) and career planning and motivation to work (.514). It is concluded that those who are more motivated at work are more likely to engage in professional career planning. The multiple regression analysis showed that professional career planning was significantly predicted by personal interest (.438), family related factors (.237), motivation to work (.575), but not by financial benefits (.009) and peer influences (-.014). In terms of professional career planning, the model explained 48.6 percent of the variance, and the goodness of fit metrics (F-Statistic= 17.345) showed that the model suited the data well. According to the findings, financial benefits and peer influences may not have as big of an impact on management graduates’ professional career planning as personal interest, family related factors and motivation to work. Hence, this study contributes to point out the most pressing impact on management graduates while planning their professional plans.